Comparative Reservoir Limnology and Water Quality Management 1993
DOI: 10.1007/978-94-017-1096-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Limnology and management of reservoirs in Brazil

Abstract: In this paper the authors report and discuss limnological information for reservoirs in Brasil including physical, chemical and biological data in order to provide an insight into some basic mechanisms and interrelationships of forcing functions, biological and biogeochemical factors useful for management.The introduction of ecotechnological measures to control, reduce eutrophication, suspended mater input and to recover water quality, is very urgent.Basic theoretical problems of reservoirs structure and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
18

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 27 publications
0
51
1
18
Order By: Relevance
“…Initial deoxygenation of the lake was much less pronounced than that expected from information from other tropical reservoirs (Van der Lingen, 1973;Van der Heide, 1982;Barrow, 1987;Junk & de Mello, 1987;Tundisi et al, 1993) and oxygen concentrations on the water surface never dropped below 63% saturation (Table 1). However, during stratification, deoxygenation of water occurred at lacustrine regions, and oxygen concentrations in the lower layer dropped to < 1 mg.L -1 .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Initial deoxygenation of the lake was much less pronounced than that expected from information from other tropical reservoirs (Van der Lingen, 1973;Van der Heide, 1982;Barrow, 1987;Junk & de Mello, 1987;Tundisi et al, 1993) and oxygen concentrations on the water surface never dropped below 63% saturation (Table 1). However, during stratification, deoxygenation of water occurred at lacustrine regions, and oxygen concentrations in the lower layer dropped to < 1 mg.L -1 .…”
Section: Resultsmentioning
confidence: 78%
“…Its main morphometric characteristics are: length of 66.5 km; surface area of 1.600 km 2 at 82 m above sea level; volume of 21,000 hm 3 ; maximum depth of 30 m. Compared with other reservoirs built on the Paraná River (Tundisi et al, 1993) its retention time is short (< 20 days). The lake area, which was mainly covered by various types of forests, swamps, ponds and peatland soils, was deficiently cleared before the dam was closed.…”
Section: Introductionmentioning
confidence: 99%
“…Tundisi et al (1993) point out that the inhibition of the eutrophication process can be associated to phosphorous retention in the cascade of reservoirs above Itaipu, and studies accomplished by Nogueira et al (2005) (Paranepanema River) and Roberto et al (2009) (Paraná River) showed that there is a phosphorous decreasing in cascade reservoirs. In Itaipu Reservoir, the importance of impoundment in Porto Primavera dam could be observed in time scale, because this nutrient had a pronounced decline after 1998 when this reservoir was closed and started to exert major influences on limnological variables downstream.…”
Section: Discussionmentioning
confidence: 87%
“…spiroides may form large blooms during periods of long retention times and low turbulence in the Barra Bonita reservoir (27). These organisms produce considerable amount of EPS that is released into the medium in the form of colloids.…”
Section: Introductionmentioning
confidence: 99%